Widely tunable multi-wavelength Tm-doped mode-locked fiber laser - Yan, Zhiyu (2018)
We propose and demonstrate a tunable multi-wavelength Tm-doped mode-locked fiber laser. The mode-locked operation is enabled by nonlinear polarization evolution technique. The tunable operation and multi-wavelength laser emission is achieved by periodical cavity transmission modulation. The tunable range of dual-wavelength mode-locking is 1864 to 1916 nm and tri-wavelength mode-locking is 1863 to 1912 nm, respectively, which is the widest in multi-wavelength Tm-doped mode-locked fiber laser to the best of our knowledge. The system has compact structure and both the multi-wavelength laser emission and tunable operation can be realized by controlling the polarization in the fiber ring cavity.